Artificial Intelligence and Plastic Surgery Resident Education - Edward A. Luce, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. A transformation of plastic surgery resident education is crucial and necessary: a conversion from a passive to an interactive, structured format. The employment of artificial intelligence holds substantial promise to accomplish that transformation, but concerns and potential liabilities do exist.